Členki kot besedilni povezovalci - Smolej, Mojca (Jezik in slovstvo, 2004)
The article focusses on those particles whose function is not realised on the level of meaning transformation or a precise determination of meaning within parts of a text (meaning modification), but (only) on the level of textual formation or textual correlation. Particles in the role of textual connectors will be understood as textual connective devices, which express meaning and logical relaitons between sentences of parts of a text.
Keywords: Slovene; slovenščina; členek (ling.); tekstna lingvistika